Research on modelling and simulation of single-mode power split hybrid system. Issue 3 (7th July 2021) - Chu, Aihua; Yuan, Yinnan; Chen, Xiang; Tong, Zhang; Geng, Wenran; Cheng, Huijun
Aiming at an optimised single-mode compound power split hybrid system, the main operating mode of the hybrid system and the torque control strategy were developed in this paper. LMS/AMESim was used to establish the plant model of the vehicle as well as the key components of the hybrid system, while the vehicle control model was established in Matlab/Simulink. In addition, the fuel economy of a certain SUV under the NEDC road spectrum was simulated by the co-simulation model, and the simulation results were compared with the experimental results on the auto chassis dynamometer. The results demonstrated that the established simulation model is an accurate reflection of the physical reality under different road spectrum conditions. Application of the model can greatly reduce the difficulty of control strategy design and improve the efficiency of vehicle development.